2015
DOI: 10.1016/j.profoo.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of α-Cryptoxanthin, β-Cryptoxanthin, α -Carotene, and β-Carotene of Pandanus Conoideus Oil by High-performance Liquid Chromatography (HPLC)

Abstract: Pandanus conoideus is an endemic plant of Papua, Indonesia, reported to be very rich in carotenoids. The purpose of this study was to develop method for the determination of carotenoids (α-cryptoxanthin, β-cryptoxanthin, α-carotene and β-carotene) in P. conoideus oil (PO) by high-performance liquid chromatography (HPLC). sing the proposed method in this research, carotenoids content of nine clones of PO were analyzed which ranged from 5.4-138.5 ng/mg for α-cryptoxanthin, 3.9-29.4 ng/mg for β-cryptoxanthin, 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 21 publications
(23 reference statements)
0
27
0
8
Order By: Relevance
“…Oxidative stress occurs when the levels of prooxidant are higher than antioxidant. Red fruit oil contains high level antioxidant α-tocopherol and γ-tocopherol [23], low level β-carotene [24] , and has been shown to have antiosidan aktivity [22]. Many studies have shown that vitamin E is very effective against oxidative stress through the mechanism of prevention of lipid peroxidation [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress occurs when the levels of prooxidant are higher than antioxidant. Red fruit oil contains high level antioxidant α-tocopherol and γ-tocopherol [23], low level β-carotene [24] , and has been shown to have antiosidan aktivity [22]. Many studies have shown that vitamin E is very effective against oxidative stress through the mechanism of prevention of lipid peroxidation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently there have been great efforts to find safe and potent natural antioxidants from various plant sources [22] Red fruit (Pandanus conoideus Lam) grow in Papua province, Indonesia and is traditionally consumed by local communities. Oil extracted from red fruit contains high level of antioxidant vitamin E (α and γ-tocopherol) [23], low level β-carotene [24], and it show antioxidant activity [22]. Due to it's content and activity the (RFO) are potentially use to prevent preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Buah merah (Pandanus conoideus Lamk) merupakan buah lokal yang terdapat di Provinsi Papua, yaitu di daerah pegunungan Jayawijaya, Nabire, Timika, dan Manokwari (Santoso et al 2011;Achadiani et al 2013). Proses pengolahan buah merah (Gambar 1A) menghasilkan tiga komponen, yaitu minyak, air, dan pasta (Southwell & Harris 1992;Sarungallo et al 2015). Pasta buah merah adalah hasil samping (by product) pengolahan minyak buah merah (Pandanus conoideus L.) yang berbentuk semi padat .…”
Section: Pendahuluanunclassified
“…W pracy Sarungallo i in. [27] wykorzystano tę technikę wraz z detekcją UV/Vis do zbadania czterech wybranych karotenoidów (α-kryptoksantyny, β-kryptoksantyny oraz α-karotenu i β-karotenu) w indonezyjskim oleju roślinnym pandanus conoideus. Wskazano na wysoką zawartość wszystkich oznaczanych karotenoidów w badanym, nietypowym oleju roślinnym (3÷20 mg/g).…”
Section: Rys 1 Wzór Strukturalny Fitoenu -Prekursora Karotenoidówunclassified